2009
DOI: 10.1103/physrevc.80.032801
|View full text |Cite
|
Sign up to set email alerts
|

Chiral asymmetry of the Fermi surface in dense relativistic matter in a magnetic field

Abstract: It is revealed that in the normal phase of dense relativistic matter in a magnetic field, there exists a contribution to the axial current associated with a relative shift of the longitudinal momenta in the dispersion relations of opposite chirality fermions. Unlike the topological contribution in the axial current at the lowest Landau level, recently discussed in the literature, the dynamical one appears only in interacting matter and affects the fermions in all Landau levels, including those around the Fermi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
155
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(167 citation statements)
references
References 45 publications
12
155
0
Order By: Relevance
“…Other derivations and various aspects of the CSE are studied in Refs. [16,17,111,[192][193][194][195][196][197][198][199][200]. We here just stress one fact that like the CME, only the lowest Landau level is responsible to the arising of CSE.…”
Section: B Chiral Separation Effect (1) What Is the Chiral Separatiomentioning
confidence: 99%
“…Other derivations and various aspects of the CSE are studied in Refs. [16,17,111,[192][193][194][195][196][197][198][199][200]. We here just stress one fact that like the CME, only the lowest Landau level is responsible to the arising of CSE.…”
Section: B Chiral Separation Effect (1) What Is the Chiral Separatiomentioning
confidence: 99%
“…Furthermore, as shown in Refs. 38,42,44 , the chiral shift ∆ is responsible for an additional contribution to the axial current density. Also, such a dynamically generated chiral shift splits each Dirac node into a pair of Weyl nodes of opposite chirality, thus producing a Weyl semimetal from a Dirac one 45 .…”
Section: Introductionmentioning
confidence: 99%
“…The first studies of interaction effects on the chiral asymmetry of relativistic matter in a magnetic field were performed in Refs. 38,42,43 by using Nambu-Jona-Lasinio models with local interaction. In particular, it was found that the interaction unavoidably generates a chiral shift ∆ 38,42 when the fermion density is nonzero.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation behind this study is the possibilty of creating ultra strong magnetic fields in non central collisions at RHIC and LHC which are estimated to be of hadronic scale [1,2] of the order of eB ∼ 2m 2 π (m 2 π ≃ 10 18 Gauss) at RHIC, to about eB ∼ 15m 2 π at LHC [2]. The studies of the effect of magnetic field on the vacuum structure of QCD has indicated that magnetic field acts as a catalyser of chiral symmetry breaking (CSB) [3,4]. On the other hand, it has been argued recently that there is an inverse magnetic catalysis at finite baryon chemical potential [5].…”
Section: Introductionmentioning
confidence: 99%